ANALYSIS OF THE ROLE OF THE ALODOKTER APPLICATION IN THE HEALTHCARE INDUSTRY ON SOCIETY - Faeni, Dewi Puspaningtyas; Ulkhusna, Dewi Cantika Hikmah (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Indonesia strongly supports the advancement of the current digital era, the market needs that continue to increase result in the development of technology is increasingly rapid and become a major part in the development of the business world, especially in various industrial fields. Digital development has become one of the ways to survive in various globally competitive industries. Digitalization has penetrated into various industries, one of which is in the health sector. Alodokter was created as a form of application of information systems which now helps people deal with health problems. The purpose of this study is to describe how the role of Alodokter as a form of technological development through digitalization is towards the community in solving various health problems. Examining what features can be accessed by its users including the function of its usefulness to what are the obstacles in using it. While this research method is carried out with qualitative methods. The results of this study will be an explanation of how important it is to implement information systems in an organization or company in various fields including the health sector. It is also important for people to be able to understand and utilize current technological advances properly and wisely. Because basically technology was created with the aim of facilitating the running of an activity to be more effective and efficient. Indonesia strongly supports the advancement of the current digital era, the market needs that continue to increase result in the development of technology is increasingly rapid and become a major part in the development of the business world, especially in various industrial fields. Digital development has become one of the ways to survive in various globally competitive industries. Digitalization has penetrated into various industries, one of which is in the health sector. Alodokter was created as a form of application of information systems which now helps people deal with health problems. The purpose of this study is to describe how the role of Alodokter as a form of technological development through digitalization is towards the community in solving various health problems. Examining what features can be accessed by its users including the function of its usefulness to what are the obstacles in using it. While this research method is carried out with qualitative methods. The results of this study will be an explanation of how important it is to implement information systems in an organization or company in various fields including the health sector. It is also important for people to be able to understand and utilize current technological advances properly and wisely. Because basically technology was created with the aim of facilitating the running of an activity to be more effective and efficient.